2007
DOI: 10.1158/1055-9965.epi-06-1012
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the CYP19A1 (Aromatase) Gene and Endometrial Cancer Risk in Chinese Women

Abstract: Aromatase, encoded by the CYP19A1 gene, is a key enzyme in estradiol biosynthesis, which catalyzes the conversion of androstenedione and testosterone to estrone and estradiol, respectively. Given the critical role of estrogen in the development of endometrial cancer risk, we evaluated genetic polymorphisms of the CYP19A1 gene, including rs1065779, rs700519, rs28566535, rs752760, and rs1870050, in association with endometrial cancer in a population-based case-control study conducted in Shanghai, China. Genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
(55 reference statements)
1
26
1
Order By: Relevance
“…However, the majority of these studies suggest that there is no overall relationship with endometrial cancer [12,[27][28][29][30][31][32]. Specifically for the rs1800440 polymorphism of CYP1B1, two studies found no association with endometrial cancer risk [30,31], however, one study by McGrath et al (2004) revealed that women with the variant genotypes (AG + GG) had a decreased risk of endometrial cancer compared to women with the wild-type (AA) genotype [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these studies suggest that there is no overall relationship with endometrial cancer [12,[27][28][29][30][31][32]. Specifically for the rs1800440 polymorphism of CYP1B1, two studies found no association with endometrial cancer risk [30,31], however, one study by McGrath et al (2004) revealed that women with the variant genotypes (AG + GG) had a decreased risk of endometrial cancer compared to women with the wild-type (AA) genotype [28].…”
Section: Discussionmentioning
confidence: 99%
“…More than 50 gene loci have been associated with the development of obesity through genomewide association studies but few Mendelian randomization studies have been undertaken to date 157,158 . These focused on few gene loci and cancers, including polymorphisms in the CYP19A1 gene (which encodes aromatase) 159 , Figure 3 | Hypothesized steatosis-hepatocellular carcinoma pathway. In the absence of common hepatic insults, such as excess alcohol, accumulation of fat in the liver (nonalcoholic fatty liver disease (NAFLD)) is associated with chronic inflammation, known as nonalcoholic steatohepatitis (NASH).…”
Section: Causal Relationships and Mendelian Randomizationmentioning
confidence: 99%
“…4 The 1531C4T (rs10046) allele has been studied extensively, which includes its potential gender-specific association with essential hypertension, 8 increased level of estrogen, 19 breast cancer risk in Japanese populations 20 and endometrial cancer risk in Chinese women. 21 This variant, observed at 56% frequency in this study and located in haplotype block 3, exhibited a haplotype structure with IVS7-79A4G, IVS6-106 T4G, IVS6+36A4T and IVS5-16T4G (D¢¼1, r 2 ¼0.92-0.96) in block 3 (Figures 2a and b). A set of tag SNPs, which will be useful for association mapping studies, were determined (Figure 2b).…”
Section: Resultsmentioning
confidence: 61%